2018
DOI: 10.1021/acs.est.7b04732
|View full text |Cite
|
Sign up to set email alerts
|

Cost, Energy, and Environmental Impact of Automated Electric Taxi Fleets in Manhattan

Abstract: Shared automated electric vehicles (SAEVs) hold great promise for improving transportation access in urban centers while drastically reducing transportation-related energy consumption and air pollution. Using taxi-trip data from New York City, we develop an agent-based model to predict the battery range and charging infrastructure requirements of a fleet of SAEVs operating on Manhattan Island. We also develop a model to estimate the cost and environmental impact of providing service and perform extensive sensi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
101
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 158 publications
(104 citation statements)
references
References 29 publications
2
101
0
1
Order By: Relevance
“…Through trip-chaining, autonomous taxis (ATs) could radically reduce the number of vehicles required, potentially at the cost of increased vehicle turn-over and longer distances. Other environmental effects arise from the easier electrification of the fleet, the higher initial energy and material requirements of ATs, the issue of empty trips, and benefits through eco-driving and platooning [121,122,136]. The impact of ATs, carsharing and ride-hailing on overall travel demand seems to be inconclusive and may depend on many local factors.…”
Section: Me In Vehiclesmentioning
confidence: 99%
“…Through trip-chaining, autonomous taxis (ATs) could radically reduce the number of vehicles required, potentially at the cost of increased vehicle turn-over and longer distances. Other environmental effects arise from the easier electrification of the fleet, the higher initial energy and material requirements of ATs, the issue of empty trips, and benefits through eco-driving and platooning [121,122,136]. The impact of ATs, carsharing and ride-hailing on overall travel demand seems to be inconclusive and may depend on many local factors.…”
Section: Me In Vehiclesmentioning
confidence: 99%
“…In two latter studies, the impact of wait times on traveler mode choice decision is neglected. Bauer et al (2018) used an agent-based model and analyzed the cost, energy, and environmental implications of SAEV service operating in Manhattan.…”
Section: Prior Researchmentioning
confidence: 99%
“…The authors concluded that SAEVs could be operated between $0.41 US and $0.47 US per occupied mile traveled. Bauer et al [22] investigated the effects of SAEV cost components on SAEV operational costs and concluded that SAEVs could be operated between $0.29 US and $0.61 US per mile. Chen and Kockelman [23] found that as SAEV fares increase from $0.75 US to $1.00 US per mile, SAEV modal share decreases from 39% to 14%.…”
Section: Sav Service Characteristicsmentioning
confidence: 99%